Bioavailability enhancement, Caco-2 cells uptake and intestinal transport of orally administered lopinavir-loaded PLGA nanoparticles. (21st November 2016) - Joshi, Garima; Kumar, Abhinesh; Sawant, Krutika
Abstract: Nanoparticles (NPs) can be absorbed via M cells of Peyer's patches after oral delivery leading to passive lymphatic targeting followed by systemic drug delivery. Hence, the study was aimed to formulate PLGA NPs of lopinavir. The NPs were prepared by nanoprecipitation, optimized by 3 3 factorial design and characterized by TEM, DSC, FTIR studies and safety was assessed by MTT assay. In vivo pharmacokinetic studies were performed in rats. The NPs were discrete spherical structures having particle size of 142.1 ± 2.13 nm and entrapment of 93.03 ± 1.27%. There was absence of drug-polymer interaction. Confocal images revealed the penetration and absorption of coumarin-loaded NPs in Caco-2 cells and intestine after oral delivery. There was 3.04 folds permeability and 13.9 folds bioavailability enhancement from NPs. The NPs can be promising delivery system for antiretroviral drug by delivering the drug to lymph (major HIV reservoir site) via direct absorption through intestine before reaching systemic circulation.